Assessment of veterinary pharmaceutical warehouse management practices and its associated challenges in four selected zones and Bahir Dar city of Amhara regional state, Ethiopia - Wondie Mekonen, Abibo; Sintayehu, Tadilo; Endeshaw Woldeyohanins, Alem; Tefera Mekasha, Yesuneh; Weldegerima Atsbeha, Berhanemeskel (Frontiers in Veterinary Science, 2024)
A pharmaceutical warehouse is part of the pharmaceutical supply chain and is essential to maintaining the quality and efficacy of veterinary pharmaceuticals for successful animal health service delivery. However, poor storage conditions, improper handling, and inappropriate use and disposal constitute challenges for veterinary supplies in animal health services. Therefore, this study aimed to assess the existing practices and challenges in warehouse management in government veterinary clinics and private veterinary drug wholesalers in Ethiopia. A cross-sectional study was conducted on 37 veterinary health facilities in four selected zones (south Gondar, west Gondar, central Gondar, and west Gojam zones) and Bahir Dar administrative city. Zones were selected using a simple random sampling technique. Data was collected using a structured questionnaire, pre-defined and tested observational checklists, and semi-structured interview guides. Descriptive statistics were used to analyze the quantitative data, while qualitative data was analyzed using a thematic approach. The study revealed the presence of poor stock management practices, such as the absence of standard operating procedures for warehouse activities in ~59.5% of facilities surveyed. In none of the surveyed facilities, bin cards and system software utilization were satisfactory. The absence of disposal guidelines was detected in 83.8% of the facilities, and the practice of timely disposal of expired drugs was not satisfactory. Compared to the government veterinary clinics, private veterinary drug wholesalers had better storage practices (86.25%) following theoretical recommendations. The storage conditions in government clinics were rated poor at 48.3% (>80%, which is the limit to the acceptable rate for good storage conditions). The challenges of inadequate infrastructure, a lack of qualified staff, problems with the availability and affordability of pharmaceutical products, insufficient regulatory practice, and budget constraints were identified. A holistic approach involving related stakeholders should be followed to improve the existing challenges and the sector's efficiency.